Designing information environment of the future teachers of the humanities - Карабін, Оксана (Educational Dimension, 2013)
Carаbin O. J. Designing information environment of the future teachers of the humanities. The article deals with the concept of information environment in the formation of future teachers of humanities, selected steps of creating an informative environment in the system of training of teachers of humanities, the basic theoretical and methodological position, which should be based design information environment and their level, the basic provisions for which should be based design information environment of the future teachers of humanities, isolated design elements of this environment.